Evolution and impact of molecular glue research: a bibliometric analysis from 2000 to 2023 - Li, Dian; Cheng, Jingyi; Yuan, Zhigen; Deng, Kexin (Frontiers in Oncology, 2024)
Background: Molecular glues, which reshape E3 ligase receptors to promote targeted protein degradation, are emerging as a promising therapeutic strategy, particularly in oncology, driven by rapidly advancing insights into their mechanisms and structural properties. Objective: This study aims to offer an insightful depiction and visualization of the knowledge structure, prevalent themes, and emerging trends within the domain since the year 2000, employing bibliometric analysis to achieve this goal. Methods: To conduct this research, a comprehensive collection of literature on molecular glues was sourced from the Web of Science database. Subsequently, the data underwent analysis utilizing CiteSpace and VOSviewer tools, enabling the identification of pivotal countries, institutions, authors, and journals, as well as the delineation of subject hotspots, trends, and the forefront of research in this evolving field. Result: Since 2000, 388 papers on molecular glues have been published, with a notable increase to an annual average of 43 articles post-2018. This research, contributed by 506 authors across 329 institutions, highlights the United States and China as leading nations in output, with 122 and 104 articles respectively. Takuzo Aida, Luc Brunsveld, and Christian Ottmann are identified as key authors. Nature emerges as the foremost publication venue, while the Chinese Academy of Sciences is the top contributing institution, underscoring the global engagement and interdisciplinary nature of molecular glue research. This study identified 19 distinct research clusters within the molecular glues domain. Conclusion: We reveal the current status, hotspots, and trends of molecular glue research since 2000, offering insights and novel scholarly perspectives on the field’s prevailing limitations.